Growth and Survival Rate of Tilapia (Oreochromis niloticus) Larvae Fed by Daphnia magna Cultured With Organic Fertilizer Resulted From Probiotic Bacteria Fermentation - Vivi Endar Herawati; Johannes Hutabarat; . Pinandoyo; Ocky Karna Radjasa (Bogor Agricultural University, Indonesia, 2015)
Daphnia magna is a potential feed for fish. The aim of this research was to find the best treatment and effect of D. magna culture addition from fermented organic fertilizer, to growth and survival rate of Oreochromis niloticus larvae. There were five treatments, each with three repetitions used in the study. All treatments used chicken dung, and different combinations of rice bran, coconut oilcake waste and tilapia larvae. Feeding on tilapia was given by ad libitum method for five times a day until 14 days. Water quality during the research was maintained at temperature 28–29°C, DO 0.3 ppm and pH 8.1–8.2. Observed variables include relative growth rate, survival rate, food consumption rate and water quality. Our results showed that D. magna cultured by fermented organic fertilizer for tilapia larvae (O. niloticus) had high significant effect (p < 0.01) on the relative growth rate and survival rate. Treatment of D. magna cultured by 1.2 g/L chicken manure, 0.9 g/L rice bran and 0.3 g/L coconut oilcake showed the highest value on the relative growth rate (10.86%); survival rate (98.46%) and food consumption at first week (106.43%) and second week (152.76%).